Three-dimensional topology optimization of Ni-YSZ anode for solid oxide fuel cells via multiphase level-set method. (1st December 2022) - He, An; Gong, Jiaming; Onishi, Junya; Shikazono, Naoki
Abstract: In the present study, numerical model is developed to optimize the 3D multiphase electrode microstructure for SOFC, e.g. nickel-yttria-stabilized zirconia (Ni-YSZ) anode. During the optimization, Ni-YSZ microstructure is deformed in order to maximize the total reaction current. Multiphase level-set (MLS) model is applied to represent the Ni-YSZ anode microstructure, and adjoint method is applied for the sensitivity analysis. In addition, in order to improve the computational accuracy and to make the optimized microstructure manufacturable, a radius constraint is imposed to ensure that the local particle radii are kept larger than a target value ( R target ), where the interface is updated only when the local radius value is larger than R target . It is also confirmed that the optimized microstructure and performance of the Ni-YSZ anode are independent of the initial structures and the phase division schemes. According to the optimization results, the optimized electrochemical performances are improved, and the particle and pore radii of the microstructure successfully remained larger than the target values. The optimized Ni-YSZ microstructures are composed of Ni particles embedded into a YSZ scaffold which has a pillar-like shape along the anode thickness direction. Graphical Abstract: ga1 Highlights: Optimization model is developed for multi-phase structure, e.g. Ni-YSZ. Multiphase level set method is adopted to represent Ni-YSZ microstructure. Optimized Ni-YSZ structure dramatically enhances the reaction current. The optimized structure has Ni particles embedded into pillar shaped YSZ scaffold. Effects of target radius and grid dependency are investigated.